PKM Cultivation Development and Sweet Corn Milk Production Sulangai Village, Petang District, Badung Regency - Udayana, I Gusti Bagus; Tantra, I Gusti Lanang Putu; Wirajaya, Anak Agung Ngurah Mayun; Dewi, Ni Kadek Ayu Khrisna Rudhana; Risy, Ni Putu Meidy (PT FORMOSA CENDEKIA GLOBAL, 2024)
Sulangai Village is an agricultural village and is developing so that the livelihood of the population is greatly influenced by the condition of a village. Community Partnership Empowerment (PKM) has the goal for partners: increasing knowledge and skills of partners in developing sweet corn cultivation while utilizing sweet corn products to increase their added value into sweet corn milk from the Women Farmers Community in order to increase the added value of production and income, which so far has only sold its sweet corn production but is currently also being attempted to increase its income through the sale of sweet corn milk. The touch of technology in cultivating sweet corn and sweet corn production which has not been implemented properly will provide high added value for partner groups and is useful in increasing agricultural yields and increasing the income of women farmers.